Sequential Fractionation of Lignocellulosic Biomass Using CO2‐Assisted Hydrolysis Combined with γ‐Valerolactone Treatment. Issue 1 (28th October 2019) - Zhai, Qiaolong; Hse, Chung-yun; Long, Feng; Wang, Fei; Shupe, Todd F.; Xu, Junming
Abstract : A biomass biorefinery strategy for the selective fractionation of poplar into its three main compositions (hemicellulose sugars, lignin, and high‐purity cellulose) with a two‐step process is developed. The first step consists of the selective hydrolysis of hemicellulose at mild conditions in a CO2 /H2 O system. This leads to various hemicellulose sugars and other intermediates in the water‐soluble fraction, with more than 87.90% of the hemicellulose being extracted from the original poplar (180 °C, 2.0 MPa CO2, 10 min). The pretreated sample is subsequently used for extracting lignin in a γ‐valerolactone (GVL)/H2 O with acid catalysts for the next step. Meanwhile, four acid catalysts, including sulfuric acid and solid heteropoly acids (phosphomolybdic acid, silicotungstic acid, and phosphotungstic acid), are studied for the selective delignification in the GVL/H2 O system, resulting in more than 91.35% of the original lignin being removed in the cellulose‐rich substrates (140 °C, 30 mM silicotungstic acid, 3 h). Overall, the biorefinery approach fractions the poplar wood into three primary components: 1) various oligosaccharides, monosaccharides, and other intermediates derived from hemicellulose; 2) cellulose‐rich substrate with a purity of cellulose as high as 90.76%, which has great potential as biochemicals or biomaterials; and 3) high‐purity and proportion lignin recovered from biomass. Abstract : A green biomass biorefinery strategy for the selective fractionation of lignocellulose is reported. The selective hydrolysis of hemicellulose is performed in a CO2 /H2 O system. Subsequently, the extraction of lignin from the pretreated samples is conducted in a γ‐valerolactone (GVL)/H2 O system with solid heteropoly acids as the catalyst. This biorefinery strategy shows practical significance for the effective fractionation of lignocellulosic biomass.